TAHLILUL MAWADH AD DIROSIAH FI KITAB AL ARABIYAH BAINA YADAIK - Nurul Jannah (UIN ANTASARI, 2019)
Textbook is an element of the educational curriculum as well as the teaching method. The textbook influences students’ understanding, whether it has similar or different characteristics. Therefore, the textbook author must be careful in compling and developing the material. Theaching material is the forms of material used to assist the teacher in carrying out teaching activities. The material must have its own characteristics. The type of research is a qualitative research with descriptive analyisis. The data in this research is the book “Arabiyyah Baina Yadaik Juz Awwal”. The topic in this research is the analysis of the matterial, either from the advantages or this advantages, the steps in this research are: reading the books related to the material of the research, interview between students who learn the book, and analyse accurately of the research. The result of this research is the textbook is quite good in foundations and characteristics of the learning material for non-native speakers.